2015
DOI: 10.1016/j.leaqua.2014.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering the accuracy of follower leadership ratings

Abstract: (2015) 'Reconsidering the accuracy of follower leadership ratings.', Leadership quarterly., 26 (2). pp. 220-237. Further information on publisher's website:http://dx.doi.org/10.1016/j.leaqua. 2014.11.006 Publisher's copyright statement: NOTICE: this is the author's version of a work that was accepted for publication in The Leadership Quarterly. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
106
0
32

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 97 publications
(140 citation statements)
references
References 171 publications
(271 reference statements)
2
106
0
32
Order By: Relevance
“…This is because weekly measurements (compared to generalised trait assessments) more readily capture leader reactions to work events as well as subsequently displayed verbal and nonverbal behaviour (Hoffman & Lord, 2013;Ohly et al, 2010). Furthermore, weekly measurements reduce concerns regarding recall bias, which can negatively influence the accuracy of leadership ratings (Hansbrough et al, 2015). Concerns regarding recall bias may be particularly heightened for leader behaviour involving complex emotions such as emotional ambivalence or inconsistency as those behaviours are more difficult to recall (Fong, 2006).…”
Section: Theoretical Justification and Results Of Multilevel Confirmamentioning
confidence: 99%
See 3 more Smart Citations
“…This is because weekly measurements (compared to generalised trait assessments) more readily capture leader reactions to work events as well as subsequently displayed verbal and nonverbal behaviour (Hoffman & Lord, 2013;Ohly et al, 2010). Furthermore, weekly measurements reduce concerns regarding recall bias, which can negatively influence the accuracy of leadership ratings (Hansbrough et al, 2015). Concerns regarding recall bias may be particularly heightened for leader behaviour involving complex emotions such as emotional ambivalence or inconsistency as those behaviours are more difficult to recall (Fong, 2006).…”
Section: Theoretical Justification and Results Of Multilevel Confirmamentioning
confidence: 99%
“…A common criticism of experimental studies is their lack of external validity due to an artificial laboratory environment as well as a potentially unrepresentative sample (e.g., in case of student respondents; Saunders et al, 2009 Hansbrough, Lord, & Schyns, 2015), which would not be possible to achieve with a cross-sectional design (Bolger & Laurenceau, 2013). Practically, I sent out online surveys to both leaders and followers of UK-based organisations.…”
Section: Research Philisophy and Research Designs Of This Thesismentioning
confidence: 99%
See 2 more Smart Citations
“…Leniency refers to the tendency that persons describing someone they know and like are much more likely to attribute positive traits to them than negative traits. Recently, scholars have suggested that followers perceptions of leader behavior are also influenced by inferences based on semantic memory, which may vary between individuals (Hansbrough, Lord, & Schyns, 2014). Similarly by considering leader perceptions as attitudes, this review has shown that such perception can be influenced by a host of attitudinal processes that may not accurately reflect leader behavior.…”
Section: Theoretical Implicationsmentioning
confidence: 95%